Metabolic response of raw 264.7 macrophages to exposure to crude particulate matter and a reduced content of organic matter - Jankowska-Kieltyka, Monika; Roman, Adam; Mikrut, Magdalena; Kowalska, Marta; van Eldik, Rudi; Nalepa, Irena (Toxics, 2021)
Exposure to air pollution from various airborne particulate matter (PM) is regarded as a potential health risk. Airborne PM penetrates the lungs, where it is taken up by macrophages, what results in macrophage activation and can potentially lead to negative consequences for the organism. In the present study, we assessed the effects of direct exposure of RAW 264.7 macrophages to crude PM (NIST1648a) and to a reduced content of organic matter (LAp120) for up to 72 h on selected parameters of metabolic activity. These included cell viability and apoptosis, metabolic activity and cell number, ROS synthesis, nitric oxide (NO) release, and oxidative burst. The results indicated that both NIST1648a and LAp120 negatively influenced the parameters of cell viability and metabolic activity due to increased ROS synthesis. The negative effect of PM was concentration-dependent; i.e., it was the most pronounced for the highest concentration applied. The impact of PM also depended on the time of exposure, so at respective time points, PM induced different effects. There were also differences in the impact of NIST1648a and LAp120 on almost all parameters tested. The negative effect of LAp120 was more pronounced, what appeared to be associated with an increased content of metals.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Cell viability; Nitric oxide; Particulate matter; Reactive oxygen species